2016
DOI: 10.1038/srep31573
|View full text |Cite
|
Sign up to set email alerts
|

Social context affects tail displays by Phrynocephalus vlangalii lizards from China

Abstract: Competition between animals for limited resources often involves signaling to establish ownership or dominance. In some species, the defended resource relates to suitable thermal conditions and refuge from predators. This is particularly true of burrow-dwelling lizards such as the Qinghai toad-headed agama (Phrynocephalus vlangalii), which are found on the Tibetan plateau of western China. Male and female lizards occupy separate burrows, which are vital for anti-predator behaviour during warmer months when liz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 37 publications
5
28
0
Order By: Relevance
“…Here, we also observed other visuals displays in both species, such as head-bobs, charges, forelimb waves, accompanying the hemipenes eversion behavior (see Tables 1, 2 and S2). In concordance with our proposal, these behaviors are known to be used as signs of aggressiveness in other lizards (e.g., Ord 2001;Wilczynski et al 2015;Peters et al 2016). Interestingly, similar behaviors have been registered in some mammals, which also drag their penis and their anogenital region (Rozenfeld and Rasmont 1991;Ottway et al 2005) during agonistic interactions.…”
Section: Discussionsupporting
confidence: 86%
“…Here, we also observed other visuals displays in both species, such as head-bobs, charges, forelimb waves, accompanying the hemipenes eversion behavior (see Tables 1, 2 and S2). In concordance with our proposal, these behaviors are known to be used as signs of aggressiveness in other lizards (e.g., Ord 2001;Wilczynski et al 2015;Peters et al 2016). Interestingly, similar behaviors have been registered in some mammals, which also drag their penis and their anogenital region (Rozenfeld and Rasmont 1991;Ottway et al 2005) during agonistic interactions.…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, based on the rationale of natural history-dependent behavior-metabolism/performance coadaptation (Montiglio et al 2018), we hypothesized that exploration/risk-taking behavior, but not vigilance or freezing behavior, should coevolve with pace of life traits (metabolism and performance) in P. vlangalii. Our previous studies have demonstrated that freezing behavior did not correlate with locomotor performance (maximal endurance and sprint speed), consistent with this hypothesis (Peters et al 2016;Qi et al 2012;Qi et al 2014). In the present study, we firstly examine the association between exploration propensity/risk-taking and metabolic rate/performance traits in male P. vlangalii and test the coadaptation among these traits as suggested in POLS, then we compared current results and previous work and see how behavioral types play functional roles in life history trade-offs to supporting pace-of-life syndrome hypothesis.…”
Section: Manuscript To Be Reviewedsupporting
confidence: 79%
“…The territorial displays of Jacky dragons were filmed in the field using a dual camera system (see Ramos and Peters, 2017), and one display was selected as representative of the set. Using a free Matlab (Mathworks Inc) toolbox (Hedrick, 2008), we digitized the position of multiple body parts throughout the sequence and reconstructed the signaling motion in 3D (see Bian et al, 2016;Peters et al, 2016 for applications of this technique). To begin creating the 3D animation, we built the lizard model using a subdivision-modeling technique, which involves sculpturing and texturing the model using real morphological measurements and photographs of skin textures.…”
Section: Creating 3d Lizard Model and Microhabitatmentioning
confidence: 99%